2011
DOI: 10.1088/0953-8984/23/23/235106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the static properties of cluster formations in symmetric linear multiblock copolymers

Abstract: Abstract. We use molecular dynamics simulations to study the static properties of a single linear multiblock copolymer chain under poor solvent conditions varying the block length N , the number of blocks n, and the solvent quality by variation of the temperature T . We study the most symmetrical case, where the number of blocks of monomers of type A, n A , equals that of monomers B, n B (n A = n B = n/2), the length of all blocks is the same irrespective of their type, and potential parameters are also chosen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…the relative size and arrangement of the blocks [7]. The same has been shown to be true for a single multiblock copolymer chain under poor solvent conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…the relative size and arrangement of the blocks [7]. The same has been shown to be true for a single multiblock copolymer chain under poor solvent conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 57%
“…However, it has been shown that the different regimes of interest for the phase behavior can all be accessed by simulations [8-10, 13-15, 18]. Multiblock copolymers composed of two different types of blocks (A and B) alternating along the linear chain and length of a block A being equal to the length of block B that adopt coil-like structures in a good solvent or at temperatures close to the Θ [11][12][13][14][15]19] have been studied. The chemical difference of monomers should actually be kept responsible for an expansion in the chain dimensions with respect to the equivalent homopolymer chains (same total number of monomers) under the same thermodynamic conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Towards this end, computer simulations have recently made substantial strides 4,19,20,21,22,23,24,25,26,27,28,29,30,31 focusing on solutions of linear multiblock copolymers of the (A n B n ) m type, where n is the degree of polymerization of each block and m is the number of blocks. Systematic explorations within the large parameter space established quantitative relations on how copolymer architecture and intermolecular interactions determine the macroscopic phase behavior and the related chain conformations changes.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive study on the phase behavior and the static properties of linear multiblock copolymers has been presented in a series of papers by Theodorakis, et al 22,23,24,25 Molecular Dynamics simulations of single linear multiblock copolymer chains were performed under various solvent conditions. In all cases, the A and B blocks were of equal length and with the same self-energetic interactions (i.e., common solvent conditions), whereas the unmixing tendency was introduced via A-B interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation